Diagnostic Yield of Repeat Capsule Endoscopy and the Effect on Subsequent Patient Management. (2010) - Svarta, Sigrid; Segal, Brandon; Law, Joanna; Sandhar, Ajit; Kwok, Ricky; Jacques, Andrew; Lakzadeh, Pardis; Enns, Robert
Abstract : BACKGROUND: Capsule endoscopy (CE) has been shown to produce a high diagnostic yield in patients with obscure gastrointestinal bleeding (OGIB); however, in those with negative studies, management is controversial. Very few studies have reported on repeat CE in the same patient; data regarding this diagnostic strategy are limited. OBJECTIVE: To determine the diagnostic yield of repeated CE studies and how this yield affects subsequent patient management. METHODS: A retrospective chart review of all patients who underwent CE at St Paul's Hospital (Vancouver, British Columbia) between December 2001 and June 2009 was conducted. Patients who underwent subsequent repeat CE were identified and divided into one of four subgroups. Findings were classified as positive or negative. RESULTS: Eighty-two of 676 patients underwent more than one CE study. Group 1 (incomplete study) included 22 patients (27%) and yielded 10 positive findings (45%). Group 2 (screening) comprised four patients (5%) and yielded two positive findings (50%). Group 3 (ongoing symptoms despite previous negative study) totalled 26 patients (32%) and yielded 10 positive findings (38%). Group 4 (previous positive study with treatment/investigation) included 30 patients (37%) and yielded 23 positive findings (77%). Overall, the present study found positive findings in 55% (45 of 82) of repeated CE cases, which resulted in a change in management in 39% (n=32) of the patients. CONCLUSION: Due to the high diagnostic yield and noninvasive nature of CE, repeat CE appears to be of benefit and should be considered for specific patients before other types of small bowel studies.